2022
DOI: 10.1021/acsestengg.2c00068
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Water Effect for Selective Catalytic Reduction of NOx with NH3 over Cu-SSZ-13 Catalysts

Abstract: The catalytic activity of commercial Cu-SSZ-13 monolith catalysts was measured in the presence and absence of water, which demonstrated an inhibiting role below 300 °C and a promoting role above 300 °C. Furthermore, temperature-programed desorption illustrated that hydrolysis of Z 2 Cu would take place to generate ZCu II OH and [Cu(H 2 O) 6 ] 2+ species, which inhibited ammonia adsorption over Lewis acid sites but promoted nitrate formation and gaseous NO 2 desorption. The temperatureprogramed surface reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
7
1
Order By: Relevance
“…In line with our findings on CuCHA10, they observed standard SCR NO x conversion to be promoted by the presence of water in the feed. Conversely, in a recent publication, Ma et al observed the low-T deNO x activity to be inhibited by water over a commercial Cu-SSZ-13 catalyst with a Cu loading ratio of ∼1.4 wt % and SiO 2 /Al 2 O 3 ∼ 9 . Even if apparently in contrast with our results, we have to consider that, in that case, a severe aging pretreatment (at 750 °C for 16 h) was applied by the authors, leading to dealumination and decrease in the catalyst acidity .…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In line with our findings on CuCHA10, they observed standard SCR NO x conversion to be promoted by the presence of water in the feed. Conversely, in a recent publication, Ma et al observed the low-T deNO x activity to be inhibited by water over a commercial Cu-SSZ-13 catalyst with a Cu loading ratio of ∼1.4 wt % and SiO 2 /Al 2 O 3 ∼ 9 . Even if apparently in contrast with our results, we have to consider that, in that case, a severe aging pretreatment (at 750 °C for 16 h) was applied by the authors, leading to dealumination and decrease in the catalyst acidity .…”
Section: Resultscontrasting
confidence: 99%
“…With respect to the recent literature, 17,18,40,43,46,50 which mainly focuses on the effects of operating conditions (e.g., water feed content) or catalyst formulation by directly looking at the global SCR process, once again, the present results demonstrate the importance of analyzing the standard SCR process as two separate half-cycles.…”
Section: Effect Of H 2 O On Cu-cha Catalysts With Different Sarsmentioning
confidence: 65%
See 1 more Smart Citation
“…In situ DRIFT spectra and corresponding mapping were recorded for further analysis of [Cu­(OH)] + in 10-membered rings and Cu 2+ in 6-membered rings. According to the literature, two distinguished bands around 950 and 900 cm –1 are attributed to T–O–T asymmetric vibrations perturbed by [Cu­(OH)] + and Cu 2+ species for Cu-SSZ-13. These two bands of zeolite framework vibrations are perturbed by Cu species in the neighborhood of the zeolite lattice, representing the solvation of two different types of Cu species with NH 3 , namely, [Cu­(OH)] + and Cu 2+ species, respectively . Similar phenomena also appear in Cu-SAPO-34 and Cu-SAPO-18, while the FTIR bands for [Cu­(OH)] + and Cu 2+ species are around 900 and 850 cm –1 .…”
Section: Resultsmentioning
confidence: 73%
“…When humidity increased from 30 to 60%, NH 3 removal did not decrease further but actually increased in a broad range of temperature, while N 2 selectivity seemed to decrease slightly in the range of 320–400 °C. It can be speculated that H 2 O molecules can compete with NH 3 molecules for adsorption sites, while they can also help conversion of NH 3 to surface residual nitrogen compounds. , The former role of H 2 O can induce reduction of NH 3 removal; however, from a certain level of humidity, the later pathway can become more activated, leading to the improved NH 3 removal and the reduced N 2 selectivity.…”
Section: Resultsmentioning
confidence: 99%